1996
DOI: 10.1139/z96-070
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging of giant transgenic mice is associated with elevated free radical processes

Abstract: Transgenic growth hormone mice lived half as long as normal on a 23% protein diet. Longevities of both transgenic and control mice on a 38% protein diet were half those on 23% protein food. We hypothesized that transgenic mice are energetically constrained by their rapid growth, so energy supplements might improve "longevity assurance investments." As predicted, sucrose supplements extended the longevity of transgenic females (from a mean of 3 15 to 4 19 d). We measured two key biomarkers of aging (in brain, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 75 publications
5
68
0
Order By: Relevance
“…Superoxide generation has been shown to be significantly elevated in rodents overexpressing GH (66). In the current study, we found that GH transgenic mice exhibited elevated levels of oxidative protein damage to both liver and brain at different ages compared to their normal counterparts.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Superoxide generation has been shown to be significantly elevated in rodents overexpressing GH (66). In the current study, we found that GH transgenic mice exhibited elevated levels of oxidative protein damage to both liver and brain at different ages compared to their normal counterparts.…”
Section: Discussionsupporting
confidence: 56%
“…No differences in the amount of oxidized DNA (8OHdG) were detected between GH transgenic and normal mice. Lipid peroxidation was not measured in this study as previous reports indicated that indices of lipid peroxidation were significantly higher in animals with high plasma GH compared to controls (66).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We previously found that longevity of mice was negatively associated with oxidative and nitrosative stress (Rollo et al 1996;Aksenov et al 2013;Long et al 2012). Lipid peroxidation in the heart or brain of transgenic growth hormone mice expressing doubled growth rates explained~89 % of variation in maximal longevity associated with genotype, sex, and diet (Rollo et al 1996).…”
Section: Hydrogen Peroxidementioning
confidence: 99%
“…Lipid peroxidation in the heart or brain of transgenic growth hormone mice expressing doubled growth rates explained~89 % of variation in maximal longevity associated with genotype, sex, and diet (Rollo et al 1996). If free radicals do not impact aging, some are strongly associated.…”
Section: Hydrogen Peroxidementioning
confidence: 99%